The Influence of the Independence of the Board of Commissioners, Audit Quality, and Company Size on Banking Profitability - Lulu, Lulu; Sundarta, M. Imam; Muniroh, Leny; Prasetia, Angga (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2022)
The purpose of this study was to determine the effect of the independence of the board of commissioners, audit quality, and firm size on banking profitability both partially and simultaneously. The population of this study is all banks listed on the Indonesia Stock Exchange in 2019-2021. The technique for selecting the sample uses purposive sampling and the number of data samples is 39 data. This study uses secondary data in the form of financial statements of banking companies obtained from the publications of the Indonesia Stock Exchange. The results of this study indicate that audit quality has a significant effect on the direction of a positive relationship to profitability. The independence of the board of commissioners and the size of the company have no significant effect on the direction of the negative relationship to profitability.